Faktor-Faktor yang Mempengaruhi Penerimaan Premi Karyawan Panen Kelapa Sawit di PT. Socfindo Tanah Gambus Kecamatan Lima Puluh, Kabupaten Batu Bara, Sumatera Utara - Anisa Aulia Dewi; Ispinimiartriani Ispinimiartriani; Novfirman Novfirman (Mahesa Research Institute, 2024)
Oil palm harvesting is an important activity in oil palm management. The harvesting process involves cutting Fresh Fruit Bunches (FFB) from trees until the fruit arrives at the Yield Collection Point (TPH). The success of oil palm harvest is closely related to the harvester's knowledge of the harvest system, harvest ripening criteria, and harvest rotation. Employees get premiums because the employee works beyond normal working hours or overtime, works on holidays, or because of the employee's productivity work performance at work. Premium is an overpayment given by the company because employees have to work harder for various circumstances or uncomfortable working conditions. The purpose of this research is to (1). To find out what affects premiums at PT. Socfindo Tanah Gambus Kec. Lima Puluh District, Batu Bara Regency, North Sumatra, (2). To find out the influence of work experience, work motivation, age, attendance and work performance on premiums at PT. Socfindo Tanah Gambus Kec. Lima Puluh, Batu Bara Regency, North Sumatra. This research was carried out for 4 months starting from April to July. The methods used are quantitative methods and sampling techniques using Purposive Sampling. The results of the study of factors affecting premiums showed that work motivation (X2), attendance (X4) and work performance (X5) had a real effect on premiums. In this study, the most influential factor among other factors is work performance (X5) with a significant value (0.000) from the real level used, namely (0.05) or 5%, while work experience (X1) and age (X3) have no real effect on premiums because the definition value obtained from the results of data processing is greater than the real level used, which is (0.05). This study can conclude that the five factors that affect premiums are work motivation (X2) 0.0070.05 and work performance (X5) 0.0000.05 have a positive and significant effect while attendance (X4) 0.0170.05 has a negative and significant effect.